Estratégia competitiva e estratégia de produção: estudos de caso na produção de embalagens obtidas a partir de polietileno proveniente de fontes sucroalcooleiras - Motta, Gabriela Azevedo (2014)
In the search for new positions in the market, many companies have sought to differentiate their products and services, possibly reformulating their strategies. One of the possible strategies for modification is related to sustainability of the materials used in products and processes, such as plastic from sugarcane sources. The objective of this work is tried to identify the competitive strategies and manufacturing strategies adopted by companies that use plastic from sugarcane in package. To achieve this objective was opted for conducting case studies of two companies leader in their segments: a producer for the staffing industry, perfumery and cosmetics and other packaging supplier to the food industry. The first company competes with a focus on differentiation in only one segment, and its manufacturing strategy of horizontal integration of its packaging. The second company adopts a competitive strategy of differentiation in the context of the industry, and a manufacturing strategy of vertical integration of its products.